Inflammatory biomarkers and its value in predicting survival and outcome among patients with spontaneous intracerebral haemorrhage - A/L Rajapathyk, Senthil Kumar (2015)
Background Spontaneous IntraCerebral Hemorrhage (SICH) has emerged as one of the most devastating forms of stroke in recent decades. This disease is noted to carry a 30 day mortality rate of approximately 45%. An increasing number of studies have implicated a complex immune-mediated and inflammation mediated cascade of responses in the pathophysiology of SICH and the resultant neurologic outcome. Several clinical studies have demonstrated an association between inflammatory markers and outcome in patients with SICH. However, the exact relationship between serum biomarkers and functional outcomes amongst survivors has not been clearly elucidated . This study aims at providing a promising perspective and to evaluate the changes in peripheral leukocyte count (WBC count) and C-Reactive Protein (CRP) level in patients with SICH and to correlate these findings with survival and functional outcome, thus to to support and substantiate existing evidences. Methodology A prospective, descriptive and correlational study was conducted in Hospital Umum Sarawak (HUS) over the span of 2 years ( April 2013 till April 2015) . Patients with supratentorial intracerebral bleed secondary to uncontrolled hypertension, aged between 30-75 years were recruited in this study . Data pertaining to the demography ( age, gender, BP, GCS score, and co-morbidities) , clinical and radiological parameters ( site of lesion and the volume of the clot ) were collected on admission. Blood samples were taken to measure peripheral WBC count and CRP level on admission and at 72 hours of admission. Mortality and functional outcomes were determined at 6 months post ictus. Patients were recruited following fulfillment of exclusion and inclusion criteria and all obtained data was analyzed with Statistical Package for Social Sciences (SPSS) for Windows version 21.0. Results A total of 60 patients were recruited in this study. We found about 16 patients were less than or equal to 50 years old (26.7%) and 44 patients belong to the older age group of above 50 years (73.3%). Majority of patients presented with GCS score of 9/15 to 11/15 with a total of 13 patients (21.7%) in each group of 9/15, 10/15 and 11/15. The least number of patients encountered belonged to the GCS score of 14/15 – a total of 5 patients (8.3%). GCS score on admission was noted to be significantly related to 6 month functional outcome or Glasgow Outcome Scale (GOS) and overall mortality or survival (p<0.05). The morbidity and overall mortality or survival was also found to be significantly associated with volume of clot at presentation (p<0.05). WBC count was also noted to be correlating with haematoma volume at admission – patients with large haematoma volume inevitably had elevated WBC count. Age and gender was not found to be significantly related to the survival or 6 months functional outcome (p>0.05). WBC count and CRP level on admission and at 72 hours of admission noted to have relationship with overall 6 months GOS or functionality and also with overall survival (p<0.05). Total number of patients belonging to the better Glasgow Outcome Score (GOS) group (GOS 4-5) was found to comprise 20 patients (33.3%) and about 27 patients (45%) belonged to the poor GOS group (GOS 2-3) . About 13 patients (21.7%) succumbed to the disease (GOS 1). Conclusion We could conclude that via this study, it was evident that in patients with SICH, the main determinants or predictors of functional outcome at 6 months and overall survival were noted to be GCS score on admission, clot size, WBC count and CRP levels on admission and at 72 hours of admission.